On the number of solutions of some integral equations arising in radiative transfer - Ioannis K. Argyros (International Journal of Mathematics and Mathematical Sciences)
We discuss the number of solutions of some nonlinear integral equations arising in the theories of radiative transfer, neutron transport and in the kinetic theory of gases.